Combined Complementary and Alternative Therapies for the Management of a Breech Fetus: A Feasibility Study - Babbar, Shilpa; Williams, Karen B.; Vawter, Lisa (American Journal of Perinatology Reports, 2025)
Cesarean rates are rising in the United States, especially for breech presentations, which complicates 3 to 4% of term pregnancies and contributes to maternal morbidity. Complementary and alternative therapies (CT) like moxibustion, chiropractic, and hypnosis have been suggested as noninvasive options to encourage fetal version. This study assessed the feasibility and acceptability of combined CT for breech management.Women aged > 18 with a singleton breech fetus at 34 to 37 weeks engaged in three study visits within 2 weeks. The intervention included therapies such as Spinning Babies techniques, yoga postures, mindset techniques, and chiropractic adjustments. Stress levels were assessed pre- and postintervention.Of 24 referrals, 11 completed the study. No fetuses converted to vertex, but participants reported significantly reduced stress (p = 0.02). After the intervention, 54.5% opted for an external cephalic version, with a 50% success rate leading to two vaginal deliveries. All participants found the program beneficial, reporting high satisfaction with program duration, structure, and exercises.Although fetal version was not achieved, this CT-based program significantly reduced maternal stress, suggesting its value as an emotional management tool in breech pregnancies. Larger trials are needed to evaluate its efficacy in promoting fetal version and improving maternal outcomes.
Keywords: yoga; breech; spinning babies; chiropractic care; pregnancy